Comparações entre medições em tempo real da pCO2 aquática com estimativas indiretas em dois estuários tropicais contrastantes: o estuário eutrofizado da Baía de Guanabara (RJ) e o estuário oligotrófico do Rio São Francisco (AL) - Cotovicz Júnior, Luiz Carlos (2016)
Carbon dioxide (CO2) fluxes from aquatic systems are generally derived from the gradient in the partial pressure of CO2 (pCO2) between air and surface waters. In this study, we compare real-time measurements of water pCO2 using an equilibrator and non-dispersive infrared gas detector, with calculations based on pH and total alkalinity (TA) in two contrasting Brazilian estuaries: Guanabara Bay (Rio de Janeiro) and the São Francisco River Estuary (Alagoas). In Guanabara Bay, the measured and calculated values showed an excellent agreement (R2 = 0.95, p < 0.0001), without significant statistical differences between the two methods. In the São Francisco River Estuary, where the entire gradient from freshwaters to seawater could be sampled, important overestimates were found for the calculated pCO2. The overestimation was on average 71%, and reached up to 737%. This large bias in pCO2 calculation was verified at low pH and TA concentrations in freshwaters (pH < 7.5; TA < 700 μmol kg-1) possibly due to the contribution of organic alkalinity, lowering the buffer capacity of the carbonate system. As such, direct measurements of pCO2 should be considered as a priority for CO2 studies conducted in estuarine systems, particularly tropical systems where physical and biological processes are prone to significant spatial and temporal variability.